La parole de l’autre. La communication extra-terrestre dans la série « Valérian » de Christin et Mézières - Franck Thibault (ReS Futurae)
Since Les Mauvais Rêves in 1968, and then the first comic book La Cité des eaux mouvantes in 1970, the “Valérian agent spatio-temporel” comic series by Jean-Claude Mézières and Pierre Christin has developped along its 23 issues into a science fiction classic, and even, according to Stan Barets, “a classic of comics and a masterpiece of science fiction”. This article explores the way the authors gave the aliens a voice of their own. From Bienvenue sur Alflolol (1972) to the latest issues of the series, Christin and Mézières have managed to give extraterrestrial characters a real voice by using the possibilities of drawing, thus offering a new way of reading and understanding the voice of alterity.